Long‐lasting correction of in vivo LTP and cognitive deficits of mice modelling Down syndrome with an α5‐selective GABAA inverse agonist. (9th January 2020) - Duchon, Arnaud; Gruart, Agnès; Albac, Christelle; Delatour, Benoît; Zorrilla de San Martin, Javier; Delgado‐García, José María; Hérault, Yann; Potier, Marie‐Claude
Abstract : Background and Purpose: Excessive GABAergic inhibition contributes to cognitive dysfunctions in Down syndrome (DS). Selective negative allosteric modulators (NAMs) of α5‐containing GABAA receptors such as the α5 inverse agonist (α5IA) restore learning and memory deficits in Ts65Dn mice, a model of DS. In this study we have assessed the long‐lasting effects of α5IA on in vivo LTP and behaviour in Ts65Dn mice. Experimental Approach: We made in vivo LTP recordings for six consecutive days in freely moving Ts65Dn mice and their wild‐type littermates, treated with vehicle or α5IA. In parallel, Ts65Dn mice were assessed by various learning and memory tests (Y maze, Morris water maze, or the novel object recognition) for up to 7 days, following one single injection of α5IA or vehicle. Key Results: LTP was not evoked in vivo in Ts65Dn mice at hippocampal CA3‐CA1 synapses. However, this deficit was sustainably reversed for at least six consecutive days following a single injection of α5IA. This long‐lasting effect of α5IA was also observed when assessing working and long‐term memory deficits in Ts65Dn mice. Conclusion and Implications: We show for the first time in vivo LTP deficits in Ts65Dn mice. These deficits were restored for at least 6 days following acute treatment with α5IA and might be the substrate for the long‐lasting pharmacological effects of α5IA on spatial working and long‐term recognition and spatial memory tasks. Our results demonstrate the relevance of negative allosteric modulators of α5‐containing GABAA receptors to the treatment of cognitive deficits associated with DS.